2017
DOI: 10.1111/ane.12811
|View full text |Cite
|
Sign up to set email alerts
|

Screening for late-onset Pompe disease in western Denmark

Abstract: None of the screened patients had a reduced activity of the enzyme alpha-glucosidase. Although the cohort studied was small, our findings do not suggest that LOPD is underdiagnosed in patients with unspecified myopathy in western Denmark.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 20 publications
3
11
1
Order By: Relevance
“…The studies which do not suggest that LOPD is underdiagnosed in west Sweden,42 west Denmark,43 French-speaking Belgium,47 as well as the present study, may also be compatible with the low prevalence of LOPD in these regions owing to the different ethnic stratification of these patients 47…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The studies which do not suggest that LOPD is underdiagnosed in west Sweden,42 west Denmark,43 French-speaking Belgium,47 as well as the present study, may also be compatible with the low prevalence of LOPD in these regions owing to the different ethnic stratification of these patients 47…”
Section: Discussionsupporting
confidence: 87%
“…The non-participating patients were of a similar age and gender breakdown as the participating patients. The level of non-participation in the present study was similar to that in two Danish studies; in the first study,12 three instances of LOPD were discovered, whereas the second43 was negative.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our study, the prevalence of adult Pompe disease is 1.6% in patients with unclassi ed axial or limb-girdle muscle weakness/ hyperCKemia/ respiratory insu ciency. This nding is slightly lower compared with previous published studies in other populations, with a combined prevalence of 2.4% (Table 3) [8][9][10][11][12][13][14][15]. Although it was reported that there is a higher prevalence of Pompe disease in Taiwan, the patients with LOPD in Taiwan often showed onset of symptoms in their second decade of life with rapid disease progression [17,21].…”
Section: Discussioncontrasting
confidence: 54%
“…Involvement of the peripheral nerves may lead to polyneuropathy. Only few patients with LOPD may have normal GAA activity [72]. LOPD is usually less progressive than EOPD if untreated.…”
Section: Lopdmentioning
confidence: 99%